Warisan Air Panas Kaliulo sebagai Campuran dalam Memasak bagi Penduduk Kecamatan Pringapus Kabupaten Semarang Jawa Tengah - Suharwanto, Suharwanto (Jurnal Ilmiah Lingkungan Kebumian, 2020)
Kaliulo hot spring is located at Pringapus, Semarang District, Central Java. The hot spring has been used for cooking mixture by society like making krupuk (cracker) and ketupat. The result of cooking is used for consumption of the citizens themselves and for being sold to market. In the dry season, Kaliulo hot spring is not only for mixturing in cooking but also for drinking. Physical and chemistry analysis must be done to know the water quality. The quality of water based on the drinking water quality with standard from the government regulation number 82 / 2001 about water quality management and water pollution prevention. The physical analysis consists of temperature and DHL (conductivity), meanwhile chemical analysis consists of pH, SiO2, Al, Fe, Ca, Mg, Na, K, Li, Mn, NH3, Cl, SO4, HCO3, B dan H2S. The content of Na, Cl, H2S and NH3 in hot spring is exceed normally standard for drinking. Keyword: Hot Spring